Low-energy surface states in the normal state of α−PdBi2 superconductor - Choi, Hongchul (2019)
Topological superconductors as characterized by Majorana surface states have been actively searched for their significance in fundamental science and technological implication. The large spin-orbit coupling in Bi-Pd binaries has stimulated extensive investigations on the topological surface states in these superconducting compounds. Here we report a study of normal-state electronic structure in a centrosymmetric α−PdBi2 within density functional theory calculations. By investigating the electronic structure from the bulk to slab geometries in this system, we predict that α−PdBi2 can host orbital-dependent and asymmetric Rashba surface states near the Fermi energy. This study suggests that α−PdBi2 will be a good candidate to explore the relationship between superconductivity and topology in condensed matter physics.